2021
DOI: 10.1177/01640275211036966
|View full text |Cite
|
Sign up to set email alerts
|

Patterns and Processes of Intergenerational Estrangement: A Qualitative Study of Mother–Adult Child Relationships Across Time

Abstract: Drawing from the life course perspective, we explored patterns of estrangement between mothers and their adult children across time, and the processes through which these ties remained estranged, or moved in or out of estrangement. We used a prospective design in which data were collected in face-to-face semi-structured interviews with 61 older mothers about their relationships with their 274 adult children at two time points 7 years apart. We began by examining the patterns of stability and change in intergen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 54 publications
1
3
1
1
Order By: Relevance
“…This trajectory of IEC, named as “increasingly tight-knit”, accounted for more than 90% of sampled Chinese multi-child families. Different from what most Western studies concluded as stability of parent-child relationships in late life (Gilligan et al, 2022; Hogerbrugge & Silverstein, 2015; Schenk & Dykstra, 2012; Suitor et al, 2013), we observed an overall upward trend of collective IEC in the increasingly tight-knit families over the 8-year period in the Chinese context. The prevalence of such families aligns with the deeply rooted Chinese cultural value expressed in the proverb “Jia He Wan Shi Xing (家和万事兴),” meaning that a harmonious family cultivates prosperity.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…This trajectory of IEC, named as “increasingly tight-knit”, accounted for more than 90% of sampled Chinese multi-child families. Different from what most Western studies concluded as stability of parent-child relationships in late life (Gilligan et al, 2022; Hogerbrugge & Silverstein, 2015; Schenk & Dykstra, 2012; Suitor et al, 2013), we observed an overall upward trend of collective IEC in the increasingly tight-knit families over the 8-year period in the Chinese context. The prevalence of such families aligns with the deeply rooted Chinese cultural value expressed in the proverb “Jia He Wan Shi Xing (家和万事兴),” meaning that a harmonious family cultivates prosperity.…”
Section: Discussioncontrasting
confidence: 99%
“…Congruent with the perspective of collective ambivalence, in these families, older parents tended to have close affections with some specific children but becoming very estranged from the others. Similar to what Gilligan et al (2022) found in the Western families, the estranged and poor intergenerational relationships tended to continue for years. Such differentiated situation of IEC at the family level worsened gradually, although marginally, over time in Chinese families.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…Following-up on these considerations and recent research investigating adult parent-child estrangement (see, for example, Arránz Becker & Hank, 2022; Gilligan et al, 2022), the present study thus takes a longitudinal perspective to investigate sibling estrangement in adulthood. We use four waves of data from the German Family Panel (pairfam) to analyze respondents’ estrangement – conceptualized as lack of contact or emotional closeness – from up to four biological and non-biological adult siblings over a period of up to 6 years.…”
Section: Introductionmentioning
confidence: 99%